1990
DOI: 10.1149/1.2087070
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Conduction and Electron Mobilities in Molten NaCl ‐ Na Solutions

Abstract: The electronic conductivity of molten NaC1-Na solutions was determined as a function of the activity of Na at 850 ~ and 900~ by using the Wagner polarization technique. A transient technique was used to determine the diffusion coefficient and the mobility of electrons. A thermodynamic defect model was applied for calculating the concentration of defects as a function of the activity of Na in NaC1.Recent in situ investigations of surface states on semiconductors immersed in an electrolyte have centered on capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 4 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…A closer inspection found the current in the 5th hour of electrolysis to be 0.19 A at À0.05 V, 0.12 A at 0.05 V, 0.11 A at 0.15 V and 0.55 V, and 0.10 A at 0.85 V. These findings are indicative of electronic conduction through the molten salt. [33][34][35] Interestingly, in constant cell voltage electrolysis of Nb 2 O 5 pellets, 19 plotting the logarithm of the current at later times of electrolysis against the time produced an inclined linear region which was considered to have resulted from oxygen diffusion out of the metallised pellet. The slope was linked to the coefficient of oxygen diffusion in Nb metal.…”
Section: Potentiostatic Reduction Of Nb 2 O 5 Pelletsmentioning
confidence: 99%
See 1 more Smart Citation
“…A closer inspection found the current in the 5th hour of electrolysis to be 0.19 A at À0.05 V, 0.12 A at 0.05 V, 0.11 A at 0.15 V and 0.55 V, and 0.10 A at 0.85 V. These findings are indicative of electronic conduction through the molten salt. [33][34][35] Interestingly, in constant cell voltage electrolysis of Nb 2 O 5 pellets, 19 plotting the logarithm of the current at later times of electrolysis against the time produced an inclined linear region which was considered to have resulted from oxygen diffusion out of the metallised pellet. The slope was linked to the coefficient of oxygen diffusion in Nb metal.…”
Section: Potentiostatic Reduction Of Nb 2 O 5 Pelletsmentioning
confidence: 99%
“…It has been demonstrated that molten salts, particularly those of chlorides, can offer a significant level of electronic conductivity resulting from minute amounts of redox active impurities in the molten salt, such as multivalent transition metal ions and/or from the cathodically generated alkali or alkaline earth metal that is slightly soluble in the molten salt. [33][34][35] The current through this electronic conduction increases with the cell voltage, disregarding the presence of the metal oxide on the cathode. Thus, a significant amount of energy can be saved by applying a constant cathode potential to replace the constant cell voltage.…”
Section: Computer-aided Control Of the Cell Voltagementioning
confidence: 99%
“…A fraction of excess electrons, on the other hand, form mobile states with a constant low electronic mobility of the order of 0.1 cm 2 V À1 s À1 . 5,6,14,15 Such electrons are neither strongly localized nor completely free and are characterized as Drudetype electrons. Freyland and Egan 16 first described these observations consistently by a dynamical equilibrium between localized and mobile electrons: In M-MX solutions at high temperatures the local fluctuations of the potential energy influence the potential well of the liquid F-centre.…”
Section: Introductionmentioning
confidence: 99%
“…New investigations of alternative sodium itinerant electrolytes must not only be aware of this detrimental tendency but will also need to quantify the solubility of sodium metal via techniques similar to Bredig's and electronic conductivity contributions via polarization methods as developed by Wagner [94] and employed by Haarberg et al [95,96]. Current miscibility mitigation strategies [97] include (i) the use of mixtures of molten salts to decrease solubility, (ii) the operation of the device at lower temperatures, and (iii) further separation of the anode and cathode compartments to reduce the rate of back reaction.…”
Section: Corrosion Mechanismsmentioning
confidence: 99%